PENGARUH GROWTH MINDSET TERHADAP STRES AKADEMIK MAHASISWA - Supriyadi, Agatha Junita Kartika; Frisca Kirana Maharani Indira; Yuli Sulistiyono; Dina Amalia; Natri Sutanti (Edukasi: Jurnal Pendidikan, 2023)
Students who have a growth mindset tend to be able to face academic challenges and demands. This study aims to determine the effect of a growth mindset on students' academic stress levels. This research method uses a quantitative paradigm with a correlational approach to determine the relationship between a growth mindset and students' academic stress levels. The data collection technique uses two types of scales, namely the growth mindset scale and perceived academic stress (PAS). The subjects in this study were active students of the class of 2020 and 2021 at the Faculty of Education and Psychology, Yogyakarta State University. The results of this study indicate a relationship between a growth mindset and academic stress where the higher the level of a growth mindset of students, the lower the predicted stress level. The regression test results show a coefficient of 0.066, which means that 6.6% of the factors that influence a growth mindset are academic stress, and the rest is influenced by other factors.